EKSAMINASI SUATU DEKONSTRUKSI TERHADAP KONSTRUKSI HUKUM INDONESIA - Rutiningsih Maherawati (Perspektif, 2004)
The theme about examination is an interesting and important topic. As a result the corruption had spread all over Indonesia court, where most of the judges have been involved in judicial corruption, so examination is one of choice to create the real law enforcement in Indonesia.